Initiation of anti-retroviral/Trimethoprim-Sulfamethoxazole therapy in a longitudinal cohort of HIV-1 positive individuals in Western Kenya rapidly decreases asymptomatic malarial parasitemia - Kifude, Carolyne M.; Roberds, Ashleigh; Oyieko, Janet; Ocholla, Stephen; Otieno, Solomon; Waitumbi, John N.; Hutter, Jack; Smith, Hunter; Copeland, Nathanial K.; Luckhart, Shirley; Stewart, V. Ann (Frontiers in Cellular and Infection Microbiology, 2022)
Interactions between malaria and HIV-1 have important public health implications. Our previous cross-sectional studies showed significant associations between HIV-1 positivity and malarial parasitemia with an increased risk of gametocytemia. In this follow-up longitudinal study, we evaluated these associations to determine the magnitude of asymptomatic parasitemia over time, and to examine the effects of initiating Antiretroviral Therapy (ART) together with the broad-spectrum antibiotic Trimethoprim Sulfamethoxazole (TS) on asymptomatic parasitemia. 300 adult volunteers in a malaria holoendemic region in Western Kenya were enrolled and followed for six months. The study groups were composed of 102 HIV-1 negatives, 106 newly diagnosed HIV-1 positives and 92 HIV-1 positives who were already stable on ART/TS. Blood samples were collected monthly and asymptomatic malarial parasitemia determined using sensitive 18S qPCR. Results showed significantly higher malaria prevalence in the HIV-1 negative group (61.4%) (p=0.0001) compared to HIV-1 positives newly diagnosed (36.5%) and those stable on treatment (31.45%). Further, treatment with ART/TS had an impact on incidence of asymptomatic parasitemia. In volunteers who were malaria PCR-negative at enrollment, the median time to detectable asymptomatic infection was shorter for HIV-1 negatives (149 days) compared to the HIV-1 positives on treatment (171 days) (p=0.00136). Initiation of HIV treatment among the newly diagnosed led to a reduction in malarial parasitemia (expressed as 18S copy numbers/μl) by over 85.8% within one week of treatment and a further reduction by 96% after 2 weeks. We observed that while the impact of ART/TS on parasitemia was long term, treatment with antimalarial Artemether/Lumefantrine (AL) among the malaria RDT positives had a transient effect with individuals getting re-infected after short periods. As was expected, HIV-1 negative individuals had normal CD4+ levels throughout the study. However, CD4+ levels among HIV-1 positives who started treatment were low at enrollment but increased significantly within the first month of treatment. From our association analysis, the decline in parasitemia among the HIV-1 positives on treatment was attributed to TS treatment and not increased CD4+ levels per se. Overall, this study highlights important interactions between HIV-1 and malaria that may inform future use of TS among HIV-infected patients in malaria endemic regions.